2007
DOI: 10.1073/pnas.0702854104
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate in pharmacologic concentrations selectively generates ascorbate radical and hydrogen peroxide in extracellular fluid in vivo

Abstract: Ascorbate (ascorbic acid, vitamin C), in pharmacologic concentrations easily achieved in humans by i.v. administration, selectively kills some cancer cells but not normal cells. We proposed that pharmacologic ascorbate is a prodrug for preferential steady-state formation of ascorbate radical (Asc •؊ ) and H2O2 in the extracellular space compared with blood. Here we test this hypothesis in vivo. Rats were administered parenteral (i.v. or i.p.) or oral ascorbate in typical human pharmacologic doses (Ϸ0.25-0.5 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

37
698
3
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 610 publications
(757 citation statements)
references
References 42 publications
(82 reference statements)
37
698
3
2
Order By: Relevance
“…Besides, another application field is the in vitro modeling of OS damage. In contrary to Chen et al (2007) who argued that the immunodeficient mice with a xenograft is the most characterized method of predicting potential activity of a given molecule in humans, we propose a simple cellbased in vitro model (Chen et al, 2005). In fact, Chen's in vivo model induces a high level of ROS after hypoxic ischemia and cold ischemia of the xenograft and stimulates endothelial cell which might up-regulate AA transporters.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Besides, another application field is the in vitro modeling of OS damage. In contrary to Chen et al (2007) who argued that the immunodeficient mice with a xenograft is the most characterized method of predicting potential activity of a given molecule in humans, we propose a simple cellbased in vitro model (Chen et al, 2005). In fact, Chen's in vivo model induces a high level of ROS after hypoxic ischemia and cold ischemia of the xenograft and stimulates endothelial cell which might up-regulate AA transporters.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these data, the most cogent explanation of ascorbate action in inducing lipid peroxydation is by its intracellular mechanisms. Several data highlight that the most common theory of cytotoxic effect of high dose of AA is the intracellular and extracellular induction of H 2 O 2 without demonstrating whether this will translate to a clinical benefit (Chen et al, 2007;2005). Morever, despite the catalyst could not be identified; Deubzer et al (2010) suggested that it could be a metallo-protein secreted by some tumor cells (Deubzer et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pharmacological doses of AA (40.2 mM) are required to induce oxidation-dependent cytotoxicity both in vitro (Beck et al, 2009) and in vivo (Tareen et al, 2008). Cells convert ascorbate to the ascorbyl radical (A À ) with concomitant formation of H 2 O 2 in extracellular fluids (Chen et al, 2007), resulting in toxicity towards tumour cells (Rhee, 2006). However, this approach faces a possible complications in that the therapeutic synergy of the drug combination could be accompanied by deleterious side-effects, and by the possibility that the extracellular levels of H 2 O 2 main drop below 1 mM, at which concentration proliferation rather than cell death may be promoted (Rhee, 2006).…”
mentioning
confidence: 99%